The treatment of lymphangioma. Surgery versus sclerotherapy.* - Paradies, G.; Leggio, S.; Leggio, A. (European Journal of Pediatric Dermatology, 2001)
From 1979 to 2000 25 children with lymphangioma were treated. We compared the therapeutical efficacy and side effects of surgery and sclerosing treatment with OK-432, namely a lyophilised of beta-hemolitic group A attenuated Streptococcus pyogenes. Although surgery cannot be completely substituted, the sclerosing therapy leads to recovery in more than 50% of cases, with minor side effects, minor esthetical damage and shorter hospitalization. Also when slerosing therapy does not induce complete healing, it makes the subsequent surgery easier and decreases its risks.